Effect of thoracentesis on pulmonary gas exchange. Issue 10 (October 1983) - Perpiñá, M; Benlloch, E; Marco, V; Abad, F; Nauffal, D
Abstract : The effect of thoracentesis on pulmonary gas exchange was studied in 33 patients with unilateral pleural effusions of various causes. Arterial blood gases were measured before thoracentesis and at 20 minutes, two hours, and 24 hours after the procedure. In 13 patients alveolar arterial oxygen gradient (PA-ao2), physiological dead space:tidal volume ratio (VD/VT), physiological shunt, and "anatomical" shunt were also determined before and two hours after thoracentesis. The Pao2 showed a significant increase at each time, reaching a maximum at 24 hours (mean (SD) increase 1.1 (0.74) kPa; 8.17 (5.57) mm Hg). A concurrent significant decrease of PA-ao2 was observed (mean (SD) 1.72 (0.77) kPa; 12.92 (5.78) mm Hg). This was accompanied by a small but significant decrease of "anatomical" shunt (2.4% (1.5%] and a greater decrease of the physiological shunt (6.5% (4.3%], while VD/VT did not change. The results are probably due to improved ventilation perfusion relationships with, in particular, an increase in the ventilation of parts of the lung previously poorly ventilated but well perfused.